MENGEMBANGKAN KEMANDIRIAN MELALUI MEDIA FILM ANIMASI “UPIN DAN IPIN” PADA ANAK DIDIK KELOMPOK B TK WAHIDIYAH KECAMATAN MOJOROTO KOTA KEDIRI - Danang Prastyo (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
This Classroom Action Research was conducted on group B students in kindergarten. Wahidiyah Kediri City. The research is based on the observations and experiences of researchers, that the independence of students is still very low. The problem of this research is "Can learning using the animated film "Upin dan Ipin" be applied to develop the independence of group B kindergarten students. Wahidiyah Kediri City?”. Classroom Action Research with the research subjects of group B Kindergarten students. Wahidiyah Kediri City was carried out in 2 cycles, using instruments in the form of RKM and RKH, student activity observation sheets, teacher activity observation sheets and student learning outcomes. can increase the independence of students so that the hypothesis in this study can be accepted. Based on the conclusions of this study, it’s recommended that the use of the animated film "Upin dan Ipin" learning media can be carried out in learning activities in other development fields, of course with interesting learning methods and atmosphere created by the teacher. Therefore, teachers as implementers of learning must prioritize processes that support the creation of an exciting and targeted learning atmosphere.